Evaluating greenhouse gas reduction in Seremban, Malaysia: a pilot study on biogas production from organic municipal solid waste - Samsuri, Is Aizat; Mohd Yusoff, Mohd Zulkhairi; Hassan, Mohd Ali; Sharaai, Amir Hamzah; Ramli, Norhayati; Ahmad Farid, Mohammed Abdillah; Abd Hamid, Mohd Azhar; Maeda, Toshinari (Elsevier, 2025)
The growing population causes municipal solid waste (MSW) buildup, which is a major problem. National MSW output in Malaysia is estimated at 1.17 kg per capita. This issue is crucial since 29 Malaysian landfills produce 200 thousand tons of MSW per month, releasing greenhouse gasses (GHGs). Anaerobic digestion (AD) may convert MSW into biogas to lower its organic content for landfill disposal. The AD system aims to produce biogas from domestic organic waste to create a circular economy. This study also surveyed Seremban, Malaysia, inhabitants on MSW composition and disposal. The organic fraction of MSW was subjected to the pilot-scale 500 L AD reactor, resulting in a daily average biogas production of 92–262 L, where a significant proportion of the biogas constituent, ranging from 60 to 70 %, is CH4. Biogas production was shown to be enhanced by an increase in feedstock, as seen by a greater daily intake of 5 kg. SimaPro was then used to quantify the resulting GHGs emissions from the AD process. The results indicated a value of 0.215 kgCO2 equivalent for every 5 kg food waste that underwent processing. The proposed AD system exhibits a remarkable 80 % improvement in GHG emission reduction per kg of food waste processed, in comparison to existing methods. A thorough familiarity with organic waste's make-up and disposal patterns is necessary for its effective implementation. Statistics revealed that only 35.45 % of Seremban residents disposed of MSW daily, and that waste segregation rates were below 50 %. As a percentage of MSW, organic waste account for 55 %, or 0.35 kg/person/day. With a daily capacity of 20 kg for processing food waste, the proposed AD system is highly dependent on a constant organic waste supply. Instead of continuing to be inept at waste management, this effort offered an alternative. MSW poses significant environmental concerns, but the proposed pilot-scale AD system shows promise in addressing these issues and encouraging sustainable habits in local communities. At the very least, this could result in a reduction in MSW sent to landfills and GHG emissions for residents of Seremban.